2014
DOI: 10.1155/2014/138768
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Potential of Protocatechuate 3,4-Dioxygenase from Crude Extract ofStenotrophomonas maltophiliaStrain KB2 Immobilized in Calcium Alginate Hydrogels and on Glyoxyl Agarose

Abstract: Microbial intradiol dioxygenases have been shown to have a great potential for bioremediation; however, their structure is sensitive to various environmental and chemical agents. Immobilization techniques allow for the improvement of enzyme properties. This is the first report on use of glyoxyl agarose and calcium alginate as matrixes for the immobilization of protocatechuate 3,4-dioxygenase. Multipoint attachment of the enzyme to the carrier caused maintenance of its initial activity during the 21 days. Immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Romero-Silva et al (2013) reported that B u r k h o l d e r i a x e n o v o r a n s L B 4 0 0 d e g r a d e s 4 -hydroxybenzoate via the protocatechuate pathway catalyzed by 3,4-PCD. Guzik et al (2014) even found that 3, 4-PCD from S. maltophilia KB2, immobilized in calcium alginate, increased the activities degrading 2,5-dihydroxybenzoate, caffeic acid, 2,3-dihydroxybenzoate, and 3,5-dihydroxybenzoate. Our results for 3,4-PCD in R. ruber OA1 should facilitate further research into 3,4-PCD in Gram-positive bacteria, such as Rhodococcus.…”
Section: Discussionmentioning
confidence: 96%
“…Romero-Silva et al (2013) reported that B u r k h o l d e r i a x e n o v o r a n s L B 4 0 0 d e g r a d e s 4 -hydroxybenzoate via the protocatechuate pathway catalyzed by 3,4-PCD. Guzik et al (2014) even found that 3, 4-PCD from S. maltophilia KB2, immobilized in calcium alginate, increased the activities degrading 2,5-dihydroxybenzoate, caffeic acid, 2,3-dihydroxybenzoate, and 3,5-dihydroxybenzoate. Our results for 3,4-PCD in R. ruber OA1 should facilitate further research into 3,4-PCD in Gram-positive bacteria, such as Rhodococcus.…”
Section: Discussionmentioning
confidence: 96%
“…a and b). As the enzyme responsible for pyrene degradation may also act extracellularly that is why some of the workers have also suggested the use of immobilized enzyme for initial degradation of aromatic contaminants .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the microorganism immobilization method has been considered for bioremediation, including wastewater treatment. Immobilization can be defined as limiting the mobility of microorganisms or their enzymes with preservation of their viability and catalytic functions [8][9][10]; this can be achieved by forming a biofilm on the surface of a synthetic or natural support [11], therefore the physical and chemical properties of support material is of particular importance, specially factors as specific surface area, porosity, the surface homogeneity, and biocompatibility/ non-toxicity with the immobilized microorganisms, besides the consideration of low cost, raw materials availability and easy synthesis/preparation [12,13]. By increasing the availability of the substrates for the microorganisms, and a better interaction between substrates and the immobilized cells, synergistically results in an increase of the degradation rate of organic matter [14].…”
Section: Introductionmentioning
confidence: 99%